Disease characteristics of MCT8 deficiency: an international, retrospective, multicentre cohort study - (:unkn) unknown (ELSEVIER SCIENCE INC, 2020)
Background Disordered thyroid hormone transport, due to mutations in the SLC16A2 gene encoding monocarboxylate transporter 8 (MCT8), is characterised by intellectual and motor disability resulting from cerebral hypothyroidism and chronic peripheral thyrotoxicosis. We sought to systematically assess the phenotypic characteristics and natural history of patients with MCT8 deficiency. p p p Interpretation Our description of characteristics of MCT8 deficiency in a large patient cohort reveals poor survival with a high prevalence of treatable underlying risk factors, and provides knowledge that might inform clinical management and future evaluation of therapies.
Keywords: MONOCARBOXYLATE TRANSPORTER-8; PSYCHOMOTOR RETARDATION; HEART-RATE; HORMONE; MUTATIONS